Limit order books and trade informativeness - Hélena Beltran-Lopez; Joachim G. Grammig; Albert J. Menkveld (Goethe University Frankfurt, Center for Financial Studies (CFS), 2011)
In the microstructure literature, information asymmetry is an important determinant of market liquidity. The classic setting is that uninformed dedicated liquidity suppliers charge price concessions when incoming market orders are likely to be informationally motivated. In limit order book markets, however, this relationship is less clear, as market participants can switch roles, and freely choose to immediately demand or patiently supply liquidity by submitting either market or limit orders. We study the importance of information asymmetry in limit order books based on a recent sample of thirty German DAX stocks. We find that Hasbrouck's (1991) measure of trade informativeness Granger-causes book liquidity, in particular that required to fill large market orders. Picking-off risk due to public news induced volatility is more important for top-of-the book liquidity supply. In our multivariate analysis we control for volatility, trading volume, trading intensity and order imbalance to isolate the effect of trade informativeness on book liquidity.
urn:nbn:de:hebis:30-92979
Keywords: G14; 330; Price Impact of Trades; Trading Intensity; Dynamic Duration Models; Spread Decomposition Models; Adverse Selection Risk; Wertpapierhandel; Marktliquidität; Börsenumsatz; Börsenkurs; Informationseffizienz; Adverse Selection; Risiko; Schätzung; Deutschland